2020
DOI: 10.1097/icu.0000000000000640
|View full text |Cite
|
Sign up to set email alerts
|

Management of the glaucoma patient progressing at low normal intraocular pressure

Abstract: Purpose of review Patients with glaucoma with disease progression despite low or normal intraocular pressure (IOP) present special challenges to the treating clinician. Treatment goals may depend on whether patients have apparent low IOP with concurrent treatment or have low IOP at baseline without treatment. We review the diagnostic and therapeutic approaches to these patients. Recent findings Apparent progression at low IOP should start with confirmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Several previous studies have reported reduced visual field progression following a 30% reduction of IOP [ 9 , 11 , 12 , 19 , 20 ]. Notably, the Collaborative Normal-Tension Glaucoma Study group demonstrated that lowering IOP, either through medications or trabeculectomy, significantly slowed down the progression rate of visual field loss in a dose-dependent manner [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported reduced visual field progression following a 30% reduction of IOP [ 9 , 11 , 12 , 19 , 20 ]. Notably, the Collaborative Normal-Tension Glaucoma Study group demonstrated that lowering IOP, either through medications or trabeculectomy, significantly slowed down the progression rate of visual field loss in a dose-dependent manner [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of NTG patients receiving topical medical treatments [ 25 ], patients with a higher mean IOP reduction from baseline (i.e., percentage IOP reduction > 22.1%) experienced less progression than patients who achieved a lower mean IOP reduction (i.e., percentage IOP reduction < 13.3%). Wang and Singh suggested lowering IOP further as the most effective way of slowing the progression of glaucoma in patients with low IOP [ 26 ]. In the present study, the mean IOP reduction from baseline in NTG patients for the three PGAs, tafluprost, travoprost, latanoprost, was −2.20, −2.11, −1.86 mmHg, respectively, which translates to a rate of IOP reduction of 14.03%, 14.70%, and 12.28%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although several anti-glaucoma medications and surgical procedures are currently available to lower IOP, a considerable number of patients progress despite adequate treatment [ 20 ]. Therefore, therapy aimed at more than just lowering IOP would be required [ 17 ].…”
Section: Glaucomamentioning
confidence: 99%
“…Two months of systemic treatment with Δ 9 -THC resulted in toxic effects on photoreceptor cells in mice through functional loss in electroretinography and apoptosis [ 148 ]. For a detailed overview of other studies on neuroprotection in ocular diseases, the reader is referred to more extensive reviews [ 9 , 20 , 60 ]. An excellent overview on in vivo animal glaucoma models is provided by Gallo Afflitto et al [ 60 ].…”
Section: Neuroprotective Actions Of Cannabinoidsmentioning
confidence: 99%